Caffeinated energy drink consumption among adolescents and potential health consequences associated with their use: a significant public health hazard - De Sanctis, Vincenzo; Soliman, Nada; Soliman, Ashraf T.; Elsedfy, Heba; Di Maio, Salvatore; El Kholy, Mohamed; Fiscina, Bernadette (Acta Biomedica Atenei Parmensis, 2017)
Caffeinated energy drinks (EDs) are increasingly popular among adolescents despite growing evidence of their negative health effects. The consumption of EDs has seen a substantial increase during the past few decades, especially in the Western and Asian countries. EDs contain high levels of caffeine, sugar, and novel ingredients, and are often marketed through youth-oriented media and venues. The known and unknown pharmacology of the constituents of EDs poses a risk of caffeine toxicity and other ill effects when consumed by young people. Caffeine intoxication may result in tachycardia, vomiting, cardiac arrhythmias, seizures, and even death. Other health concerns related to consumption of EDs include obesity and dental enamel erosion resulting from the acidity of EDs. Coingestion of caffeine and ethanol has been associated with increased risk-taking behaviors in adolescent users, impaired driving, and increased use of other illicit substances. Several researchers have demonstrated that consuming alcohol mixed with energy drinks leads to altered subjective states including decreased perceived intoxication, enhanced stimulation, and increased desire to drink/increased drinking compared to consuming alcohol alone. Caffeine's effect on intoxication may be most pronounced when mixers are artificially sweetened, that is, lack sucrose which slows the rate of gastric emptying of alcohol. In conclusion: 1) health care providers should educate youth and their parents about the risks of caffeinated drinks; 2) emergency department clinicians should consider asking patients about ED and traditional caffeine usage and substance use when assessing patient symptoms; 3) policy makers should  increase their attention on introducing regulatory policies on television food advertising to which youth are exposed;  4) failure to comply with standards for efficacious product labelling, and absence of broader education regarding guidelines, need to be addressed and 5) further studies must be done to improve our understanding of potential negative consequences of caffeinated energy drinks on health.